(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the socio-political reasons for the process of transformation of public management into society are explained by the fact that global change lives in the process of new quantitative and qualitative changes of society. At the moment, as the main problem of the new millennium, the development of social technologies, mutual contradictions between attitudes towards changing the socio-cultural image of society, the need to resolve conflicts through strategic programming have been studied.